A multicenter study of three‐dimensional echocardiographic evaluation of normal pediatric left ventricular volumes and function. Issue 4 (8th March 2021) - Jone, Pei‐Ni; Le, Lisa; Pan, Zhaoxing; Colen, Tim; Shigemitsu, Sachie; Khoo, Nee S.; Goot, Benjamin H.; Parthiban, Anitha; Harrild, David M.; Ferraro, Alessandra M.; Marx, Gerald
Abstract: Background: Three‐dimensional echocardiography (3DE) evaluation of left ventricular (LV) volume and function in pediatrics compares favorably with cardiac magnetic resonance imaging. The aim of this study was to establish from a multicenter, normal pediatric z‐score values of 3DE left ventricular volumes and function. Methods: Six hundred and ninety‐eight healthy children (ages 0–18 years) were recruited from five centers. LV 3DE was acquired from the 4‐chamber view. A vendor‐independent software analyzed end‐diastolic volume (EDV), end‐systolic volume (ESV), stroke volume (SV), and ejection fraction (EF) using semi‐automated quantification. Body surface area (BSA)‐based z‐scores were generated. Intraobserver and interobserver variability were calculated using intraclass correlation (ICC) and repeatability coefficient (RC). Results: Z‐scores were generated for ESV, EDV, and SV. The ICC for intraobserver variability for EDV, ESV, and SV was 0.99, 0.99, and 0.99, respectively. The ICC for interobserver variability for EDV, ESV, and SV was 0.98, 0.94, and 0.98, respectively. The RC for intraobserver and interobserver variability for LV EF was 4.39% (95% CI: 3.01, 5.59) and interobserver was 7.08% (95%CI: 5.51, 8.42). Conclusions: We report pediatric z‐scores for normal LV volumes using the semi‐automated method from five centers, enhancing its generalizability. 3DE evaluation of LV volumes and EF in pediatric patients is highly reproducible.